The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae) - Sun, Jun-Zhi; Zhou, Chang-Fa (Zootaxa, 2016)
The nymphs of a new species of Eatonigenia have more modified labrum and smaller foreclaws than congeners, and the males have a more reddish-brown colored body, cerci, genitalia and more sclerotized projections of gonopores. These characters indicate a new species which is named E. zhangi sp. nov. The nymphs live in fine sandy/muddy substrates of large rivers.